Mechanisms of Relapse After CD19 CAR T-Cell Therapy for Acute Lymphoblastic Leukemia and Its Prevention and Treatment Strategies - Xu, Xinjie; Sun, Qihang; Liang, Xiaoqian; Chen, Zitong; Zhang, Xiaoli; Zhou, Xuan; Li, Meifang; Tu, Huilin; Liu, Yu; Tu, Sanfang; Li, Yuhua (Frontiers in Immunology, 2019)
Chimeric antigen receptor (CAR) T-cell therapy is highly effective in the treatment of B-cell acute lymphoblastic leukemia (ALL) or B-cell lymphoma, providing alternative therapeutic options for patients who failed to respond to conventional treatment or relapse. Moreover, it can bridge other therapeutic strategies and greatly improve patient prognosis, with broad applicable prospects. Even so, 30-60% patients relapse after treatment, probably due to persistence of CAR T-cells and escape or downregulation of CD19 antigen, which is a great challenge for disease control. Therefore, understanding the mechanisms that underlie post-CAR relapse and establishing corresponding prevention and treatment strategies is important. Herein, we discuss post-CAR relapse from the aspects of CD19-positive and CD19-negative and provide some reasonable prevention and treatment strategies.